2001
DOI: 10.1177/0146167201274007
|View full text |Cite
|
Sign up to set email alerts
|

Seeing One’s Partner Through Intimacy-Colored Glasses: An Examination of the Processes Underlying the Intimacy Goals-Relationship Satisfaction Link

Abstract: This research extends previous work demonstrating that individuals with intimacy goals experience greater relationship satisfaction by examining three distinct processes that may underlie this association (e.g., engaging in intimacy-conducive interactions with their partners, having intimacy-focused partners, perceiving partners as intimacy focused). The study included 100 female college students who completed measures of intimacy goals, patterns of relationship interaction, perceptions of their partner’s inti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 52 publications
8
45
0
Order By: Relevance
“…More specifically, spouses who experienced more intimacy in their relationship felt more supported by their partner, and were more positive and less negative in soliciting and providing support. These results are in line with prior research on the association between intimacy goals and support-related variables (Sanderson & Evans, 2001). The association between the level of intimacy spouses experienced in their relationship and support in their relationship proved to be consistent across gender, and across the different components of spousal support that were included in the current study.…”
Section: Summary Of Resultssupporting
confidence: 91%
“…More specifically, spouses who experienced more intimacy in their relationship felt more supported by their partner, and were more positive and less negative in soliciting and providing support. These results are in line with prior research on the association between intimacy goals and support-related variables (Sanderson & Evans, 2001). The association between the level of intimacy spouses experienced in their relationship and support in their relationship proved to be consistent across gender, and across the different components of spousal support that were included in the current study.…”
Section: Summary Of Resultssupporting
confidence: 91%
“…5, No. 4;2013 others (Sanderson & Evans, 2001). Difficulty to express emotions and understanding the emotions of others is one of the characteristics of alexithymia.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of emotion as a basic factor in intimacy development Waldinger et al, 2004) is one of the indicators of marital satisfaction. Mutual expression of emotion can also create safety and support for couples and increase self-disclosure (Sanderson & Evans, 2001). Research has indicated that self-disclosure has positive relationship with marital satisfaction (Lippert & Prager, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Avoidant attached individuals are so cold in their relationships and are not able to create intimacy . One of the factors that create intimacy in the relationship is self-disclosure (Sanderson & Evans, 2001). Difficulty expressing emotions and understanding other's emotions is a feature of alexithymia.…”
Section: Discussionmentioning
confidence: 99%